Stimulate the production of antibiotics using local isolates of the genus Streptomyces using chemical and physical mutants - Mohammed Qasim; Safaa Alobaidi; Arwa thannon (College of Education for Pure Sciences, 2014)
Three local isolates of the genus Streptomyces were obtained from ten soil samples collected from different places of Niniva governorate. The isolates showed bioactivity against test Gram positive and negative bacteria and two Genera of fungi. Streptomyces isolates were identified according to microscopic and morphological tests. The Streptomyces isolates were subjected to ultra violet ray for different time periods. The treated isolates showed little increase in inhibition zone and treated period of (5) minutes showed the best inhibition of the test bacteria. The Streptomyces isolates treated with N - methyl - N - nitro - N - nitroso guaniction at the concentration of (50)  showed clear increase of antibiotic production. The isolate Streptomyces III showed clear inhibition against Escherichia coli, Pseudomonas aeruginosa and Bacillus subtilis and the diameter inhibition zone was (20,29,20)mm respectively.